PERUBAHANGEJALA KLINIS (GASTRIC OUTLET OBSTRUCTION DAN BILIARY OBSTRUCTION) PADA PENDERITA KARSINOMA KAPUT PANKREAS SETELAH DILAKUKAN OPERASI SHUNTING BILIODIGESTIVE DI RSUP DR SARDJITO YOGYAKARTA TAHUN 2009-2013 - , Eko Purnanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Pancreatic and periampullary carcinomas are a major public health problem throughout most of the world. Pancreas cancer is the fourth leading cause of cancer death in the United States, with 31,800 deaths in 2005 as opposed to 163,510 deaths for lung cancer, 56,290 deaths for colorectal cancer, and 40,870 deaths for breast cancer.. Pancreatic carcinoma is the fourth cause of death from cancer in the United States, with a survival rate at 5 years of less than 5 %. About 60 % of tumors originate at the head of the pancreas, 15 % in the body, 5 % in the tail